PERUBAHAN KEBIJAKAN LUAR NEGERI KANADA TERHADAP IRAN PADA MASA PEMERINTAHAN STEPHEN HARPER - Bahjatul Murtasidin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research aims to analyze Canadian foreign policy change to Iran underStephen Harper as new Canadian prime minister under conservative party.This study applies qualitative research method with library research. The datasources are books, journals, and valid news from websites. To analyze theresearch question, the writer uses realist perspective, on theory of rational actor byGraham T. Allison, and level of analyze is nation-state.The research shows that under conservative party, Stephen Harper have changeCanadian foreign policy from liberalist to realist and committed to be activelyinvolved in the peace and security of the world. While Iran committed to continuenuclear development programme, based on Ideology of Conservative Party,Canada feel’s threatened and calling Iran’s goverments as the most significantthreat to global peace and security in the world today and should severed relationswith Iran.Key word: Stephen Harper,Conservative party, Canadian foreign policy, threat,severed relations